Profesor Tadeusz Sulimirski, współorganizator szkolnictwa polskiego na uchodźstwie w latach 1941–1947 - Chmielewski, Witold (Biuletyn Historii Wychowania, 2019)
The aim of the article is to present the achievements of Professor Tadeusz Sulimirski, an archaeologist, in reference to organising and managing Polish education in exile, 1941–1947. The biographical method prevails in this research paper, presenting one of the leading figures in the Office of Education and School Affairs, as well as the Ministry of Religious Denominations and Public Enlightenment of the Polish government in exile. Tadeusz Sulimirski launched numerous initiatives aimed at developing and streamlining all the forms of Polish education in exile. He cooperated very closely with General Józef Haller. He devoted much attention to developing Polish higher education in exile. Once the Polish government in London was no longer recognised by the British government, Professor Tadeusz Sulimirski became head of the Department of Education, formed on 7 July 1945, of The Interim Treasury Committee for Polish Questions established by the British. He demonstrated great creativity and organizational skills, while very competently coordinating the gradual discontinuation of Polish education in Great Britain and, to some extent, in some of the British dominions. He took great care of the financial situation of Polish students in Great Britain and in the Middle East. He also received students and schools from General Władysław Anders’ Polish II Corps evacuated from Italy to Great Britain. In the post-war years he was an active member of Polish academic circles. He greatly contributed to the development of Polish education in exile and to establishing Polish identity among war refugees.